TIPS Pentacene as a Beneficial Interlayer for Organic Photodetectors in Imaging Applications - Montenegro Benavides, Cindy; Biele, Markus; Schmidt, O.; Brabec, Christoph; Tedde, S. F. (IEEE Transactions on Electron Devices, 2018)
The small molecule 6,13-bis (triisopropylsilylethynyl) (TIPS) pentacene has been used as an interlayer for the reduction of dark currents in organic photodetectors (OPDs) based on a bulk heterojunction of poly-3-hexyl-thiophene(P3HT) and [6, 6]-phenyl C61 butyric acid methyl ester. We report OPDs with dark currents of ∼0.9 nA/cm2 at −5 V and external quantum efficiencies close to 80% at 530 nm. Compared to the reference, P3HT interlayer, TIPS pentacene shows a significant increase of the OPD’s detectivity from 3.29 × 1012 to 1.63 × 1013 Jones. Also, the OPD’s dynamic range is improved reducing the limit of signal detection from 132 to 6.3 nW/cm2 under green light irradiation. Singular hysteresis in the I–V characteristic curve has been observed and impedance spectroscopy measurements were carried out to analyze its origin and generate a replacement electrical model for the device at reverse bias. Finally, OPDs with TIPS pentacene interlayer have been integrated on top of amorphous silicon thin-film transistor backplanes to obtain the first OPD-based image sensor using this interlayer.
Keywords: Capacitance; Dark current; Electrodes; Frequency measurement; image sensor; Image sensors; Indium tin oxide; low dark current; organic photodetectors (OPDs); Pentacene; Photodetectors; triisopropylsilylethynyl (TIPS) pentacene interlayer